AFTER THE FIFTH CONGRESS OF KPPSI: SHARI`AH ON THE GROUND OF KPPSIS POLITICAL AGENDA (A CRITICAL ANALYSIS OF AN-NA`IM STANDPOINTS) - Achmad Fawaid (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2016)
This paper is aimed to reveal An-Naims idea of constitutionalism, human rights, and citizenship in reading the phenomena of some activists struggle for enforcing Shariah in South Sulawesi. It is important to notice that todays debatable issue is about to what extents Shariah can be implemented in Indonesia and how it should be tolerated by Muslims and non-Muslims living there. For such reason, reading An-Naim who has focused on Sharia in a secular state, is necessary. This study has efforts to critically respond An-Naim in the case of KPPSI (Preparatory Committee for the Implementation of Shariah), a committee that believes that special status for South Sulawesi to implement Shariah will be the best solution for Indonesian, especially in South Sulawesi. The discussion is generally divided into three parts: (1) exploring An-Naims points of views, especially in regard with Shariah and secular state; (2) a short description of KPPSI, either about its historical phases or political agenda, in enforcing Shariah in South Sulawesi; and (3) a critical view of Shariah on the ground by which the KPPSI will be used as a case to reconsider about paradoxical applicability of An-Naim notion on Shariah in secular state. To conclude, the important remarks are provided in the end of this paper.